A theory-based evaluation of a dissemination intervention to improve childcare cooks' intentions to implement nutritional guidelines on their menus. (December 2015) - Yoong, Sze; Jones, Jannah; Marshall, Josephine; Wiggers, John; Seward, Kirsty; Finch, Meghan; Fielding, Alison; Wolfenden, Luke
Abstract Background Childcare services represent a key setting to implement nutritional interventions to support the development of healthy eating behaviours in young children. Childcare-specific nutritional guidelines outlining recommendations for provision of food in care have been developed. Despite this, research suggests that few childcare services currently implement these guidelines. This study aimed to examine the impact of providing printed educational materials on childcare service cooks' intentions to use nutritional guidelines and provide fruit and vegetables on their menu. Findings A randomised controlled trial was conducted with 77 childcare services (38 control and 39 intervention). Intervention service cooks were mailed a two-page educational material together with a menu planning checklist. Intervention development and evaluation was guided by the theory of planned behaviour. Outcome data assessing intentions to use nutritional guidelines and serves of fruit and vegetables provided on menus (primary outcomes) as well as secondary outcomes (attitudes, behavioural regulation and social norms) were collected via a telephone interview with cooks. Relative to the comparison group, cooks in the intervention arm had significantly higher intentions to use the guidelines (p value 0.0005), accompanied by significant changes in perceived behavioural control (p value 0.0008) and attitudes (p value 0.0071). No significant difference in serves of fruit (p value 0.7278) and vegetables (p value 0.0573) was observed. Conclusions The use of educational materials can improve childcare service cooks' intentions to use nutritional guidelines; however, as a standalone strategy, it may not improve provision of food on menus.